Skip to content

10.21 Proof

Axioms are assumed to be true and (theorem, proposition, lamma, corollary,...) need a proof.

  • Each theorem should be deduced the axioms.
  • In a proof, we assume previous knowledge.

Two kind of Proof

Theorem: \(P\)

Direct Proof

We produce a chain of statement with end \(P\).

Each statement is the chain should follow from the predecessors and from assumed knowledge.

Example

\((-1)(-1)=1\)

Proof

We know \(1+(-1)=0\) by definition of \(-1\)

We multiply by \(-1\) and get \((-1)(1+(-1))=(-1)\cdot 0=0\)

Then \(-1+(-1)(-1)=0\)

We add \(1\) to both sides and obtain \(1+(-1)+(-1)(-1)=1+0\)

Then \(0+(-1)(-1)=1\), then \((-1)(-1)=1\)

Proof by Contradiction

We assumed that \(P\) is false and need to incorporate \(\neg P\) to sour previous knowledge.

We now apply the direct proof to get \(Q\wedge\neg Q\) for some proposition \(Q\).

This is a contradiction.

Therefore, \(P\) must be true.

Example

\(1>0\)

Proof

Assume \(1\leq 0\), by axiom \(1\neq 0\)

Thus by trichotomy, \(1<0\)

We apply the sign rules: \(1<0\) and \(1<0\) \(\Rightarrow\) \(1\cdot 1>0\cdot 1\Rightarrow 1>0\)

We obtain \(1>0\) and \(1<0\) which is a contradiction,

Therefore \(1>0\)

Other form proof

Proofs for \(P\Rightarrow Q\)

Direct method

\(P\) \(Q\) \(P\Rightarrow Q\)
T T T
T F F
F T T
F F T

Since if \(P\) is false, then \(P\Rightarrow Q\) must be true.

We only need to prove that \(P\Rightarrow Q\) is true when \(P\) is true. In that case we need to show that \(Q\) is also true.

Proof

Assume \(P\) is true

Then ..... to prove \(Q\) is true (use previous knowledge)

Hence \(Q\) is true

Example

Let \(x,y\in \R\), if \(x<-4\) and \(y>2\) (\(P(x,y)\)), then the distance from \((x,y)\) to \((1,-2)\) (\(Q(x,y)\)) is at least \(6\).

The question is the form like \(P\Rightarrow Q\), then we can apply the above method.

\(Q(x,y)=\sqrt{\left(x-1\right)^2+\left(y+2\right)^2}\geq6\equiv\left(x-1\right)^2+\left(y+2\right)^2\geq36\)

Proof

Assume \(x<-4\) and \(y>2\) is true.

Then \(x-1<-5\) and \(y+2>4\) \(\Rightarrow\) \((x-1)^2>25\) and \((y+2)^2>16\)

Then \((x-1)^2+\) \((y+2)^2>41> 36\)

Hence \(\sqrt{\left(x-1\right)^2+\left(y+2\right)^2}>\sqrt{41}>6\)

Then the distance from \((x,y)\) to \((1,-2)\) is at least \(6\).

Proof by contrapositive

Recall: \(P\Rightarrow Q\equiv\neg Q\Rightarrow\neg P\), thus we can prove \(P\Rightarrow Q\) by proving \(\neg Q\Rightarrow \neg P\) (direct method)

Proof

Assume that \(Q\) is false, then prove \(P\) is false (use previous knowledge)

Hence \(P\) is not true

Example

Let \(n\in \N\). If \(m^2\) is even then \(m\) is even.

The form is like \(P\Rightarrow Q\).

Instead of proving \(P\Rightarrow Q\), we try to use contrapositive.

Proof

Assume \(m\) is odd, then we need to prove \(m^2\) is odd

Since \(m\) is odd, so \(m=2k+1\) for some \(k\in \Z\)

Now, \(m^2=(2k+1)^2=4k^2+4k+1=2\left(2k^2+2k\right)+1\)

Since \(2k^2+2k\) is an integer, we get that \(m^2\) is odd.

Thus we complete the proof.

Proofs for \(P\wedge Q\)

Proof: We first prove \(P\)...

We now prove \(Q\)....... (use \(P\) as part of previous knowledge)

Proofs for \(P\vee Q\)

Recall \(P\vee Q\equiv \neg P\Rightarrow Q\) (can be proved by truth table)

Proof: Assume that \(P\) is false.

Then we prove \(Q\)......... (use \(\neg P\) as a part of previous knowledge)

Proof for \(P\vee Q\Rightarrow R\)

We use \(P\vee Q\Rightarrow R\equiv\left(P\Rightarrow R\right)\wedge\left(Q\Rightarrow R\right)\)

Proof: We first prove \(P\Rightarrow R\) .....

We now prove \(Q\Rightarrow R\) ........

Example

Let \(M\in \Z\). Then \(m(m+1)\) is even.

The question is equivalent to: If \(m\) is even or \(m\) is odd, then \(m(m+1)\) is even.

Proof

We first prove that if \(m\) is even then \(m(m+1)\) is even.

If \(m\) is even, then \(m=2k\) for some \(k\in\Z\).

Then \(m(m+1)=2k(2k+1)=2(k(2k+1))\) is even

If \(m\) is odd, then \(m=2k+1\) for some \(k\in \Z\)

Then \(m(m+1)=(2k+1)(2k+2)=2(2k+1)(k+1)\) is even

Thus \(m(m+1)\) is even for \(m\in\Z\)

Proof for \(P\Leftrightarrow Q\)

Recall \(P\Leftrightarrow Q\equiv\left(P\Rightarrow Q\right)\wedge\left(Q\Rightarrow P\right)\)

Proof: We first prove \(P\Rightarrow Q\) ...

Now we prove \(Q\Rightarrow P\)

Proof 2: \(P\) iff \(P_2\) iff \(P_3\) iff ..... iff \(P_n=Q\).

Example

Given a right triangle with hypotenuse \(c\) if and only if \(c^2=a^2+b^2\)

We use \(c^2=a^2+b^2-2ab\cos\theta\)

Proof: The triangle is a right triangle with hypothenuse \(c\) iff \(\theta=\frac{\pi}{2}\) iff \(cos\theta =0\) iff \(c^2=a^2+b^2\)

Proofs for \(\exists xP(x)\)

By construction: We exhibit some \(a\) in the universe such that \(P(a)\) is true.

Existential: We show that there exists some \(a\) for which \(P(a)\) is true, but we don't tell what \(a\) is

By contradiction: Assume that \((\forall x)\neg P(x)\) or assume that \(P(x)\) is false for all \(x\in U\)

Example

  1. \(\exists n \in \N\) such that \(n^2-3n+43\) is composed.

    Proof

    Let \(n=43\). Then for this \(n\), we have \(43^2-3\cdot 43+43=43\cdot 41\)

  2. \(\exists x\in (0,1)\) such that \(x^2+x-1=0\)

    Proof

    Let \(f(x)=x^2+x-1\). This function is continuous and satisfies \(f(0)=-1\) and \(f(1)=1\)

    By the Intermediate Value Theorem, there is some \(\xi\in(0,1)\) such that \(f(\xi)=0\)

    Therefore \(\xi^3+\xi-1=0\)

  3. Theorem: 1. \(\neg ((\exists x)P(x))\equiv (\forall x)(\neg P(x)\)

    Proof

    Let \(U\) be a universe for \(P(x)\)

    \(\neg((\exists x)P(x))\) is true iff \((\exists x)P(x)\) is false iff the true set for \(P(x)\) is empty iff \(P(x)\) is false for any \(x\in U\) iff \(\neg P(x)\) is true for any \(x\in U\equiv (\forall x)\neg P(x)\) is true.

    Theorem: 2. \(\neg ((\forall x)P(x))\equiv (\exists x)(\neg P(x))\)

    Proof

    \(\neg((\forall x)P(x))\) is true iff \((\forall x)P(x)\) is false iff there is a \(x\) such that \(P(x)\) is false iff \(\exists x \neg P(x)\) is true

Proof for \((\forall x)P(x)\)

Direct method: We prove for any \(x\in U\), \(P(x)\) holds

By contradiction: Suppose \((\exists x)\neg P(x)\) and get a contradiction

Definition (counter examples)

How to show that \((\forall x)P(x)\) is false?

\((\forall x)P(x)\) is false iff \(\neg(\forall x)P(x)\) is true iff \((\exists x)\neg P(x)\) is true iff there is some \(a\) such that \(P(a)\) is false.

Such element is called a counter example(反例).